Haematological and fibrinolytic status of Nigerian women with post-partum haemorrhage - Ian Roberts; Haleema Shakur; Bukola Fawole; Modupe Kuti; Oladapo Olayemi; Adenike Bello; Olayinka Ogunbode; Taiwo Kotila; Chris O. Aimakhu; Tolulase Olutogun; Beverley J. Hunt; Sumaya Huque (BMC, 2018)
Abstract Background Early treatment with tranexamic acid reduces deaths due to bleeding after post-partum haemorrhage. We report the prevalence of haematological, coagulation and fibrinolytic abnormalities in Nigerian women with postpartum haemorrhage. Methods We performed a secondary analysis of the WOMAN trial to assess laboratory data and rotational thromboelastometry (ROTEM) parameters in 167 women with postpartum haemorrhage treated at University College Hospital, Ibadan, Nigeria. We defined hyper-fibrinolysis as EXTEM maximum lysis (ML) > 15% on ROTEM. We defined coagulopathy as EXTEM clot amplitude at 5 min (A5) < 40 mm or prothrombin ratio > 1.5. Results Among the study cohort, 53 (40%) women had severe anaemia (haemoglobin< 70 g/L) and 17 (13%) women had severe thrombocytopenia (platelet count < 50 × 109/L). Thirty-five women (23%) had ROTEM evidence of hyper-fibrinolysis. Based on prothrombin ratio criteria, 16 (12%) had coagulopathy. Based on EXTEM A5 criteria, 49 (34%) had coagulopathy. Conclusion Our findings suggest that, based on a convenience sample of women from a large teaching hospital in Nigeria, hyper-fibrinolysis may commonly occur in postpartum haemorrhage. Further mechanistic studies are needed to examine hyper-fibrinolysis associated with postpartum haemorrhage. Findings from such studies may optimize treatment approaches for postpartum haemorrhage. Trial registration The Woman trial was registered: NCT00872469; ISRCTN76912190 (Registration date: 22/03/2012).